TLR3 drives IRF6‐dependent IL‐23p19 expression and p19/EBI3 heterodimer formation in keratinocytes. Issue 9 (25th August 2015) - Ramnath, Divya; Tunny, Kathryn; Hohenhaus, Daniel M; Pitts, Claire M; Bergot, Anne‐Sophie; Hogarth, P Mark; Hamilton, John A; Kapetanovic, Ronan; Sturm, Richard A; Scholz, Glen M; Sweet, Matthew J
Abstract : Interferon regulatory factor (IRF) family members impart cell‐type specificity to toll‐like receptor (TLR) signalling, and we recently identified a role for IRF6 in TLR2 signalling in epithelial cells. TLR3 has a well‐characterized role in wound healing in the skin, and here, we examined TLR3‐dependent IRF6 functions in human keratinocytes. Primary keratinocytes responded robustly to the TLR3 agonist poly(IC) with upregulation of mRNAs for interferon‐β (IFN‐β), the interleukin‐12 (IL‐12) family member IL‐23p19 and the chemokines IL‐8 and chemokine (C–C motif) ligand 5 (CCL5) . Silencing of IRF6 expression enhanced poly(IC)‐inducible IFN‐β mRNA levels and inhibited poly(IC)‐inducible IL‐23p19 mRNA expression in primary keratinocytes. Consistent with these data, co‐transfection of IRF6 increased poly(IC)‐inducible IL‐23p19 promoter activity, but inhibited poly(IC)‐inducible IFN‐β promoter activity in reporter assays. Surprisingly, poly(IC) did not regulate IL‐12p40 expression in keratinocytes, suggesting that TLR3‐inducible IL‐23p19 may have an IL‐23‐independent function in these cells. The only other IL‐12 family member that was strongly poly(IC) inducible was EBI3, which has not been shown to heterodimerize with IL‐23p19. Both co‐immunoprecipitation and proximity ligation assays revealed that IL‐23p19 and EBI3 interact in cells. Co‐expression of IL‐23p19 and EBI3, as compared with IL‐23p19 alone, resulted in increased levels of secreted IL‐23p19, implying a functional role for this heterodimer. In summary, we report that IRF6 regulates a subset of TLR3 responses in human keratinocytes, including the production of a novel IL‐12 family heterodimer (p19/EBI3). We propose that the TLR3‐IRF6‐p19/EBI3 axis may regulate keratinocyte and/or immune cell functions in the context of cell damage and wound healing in the skin.